The Effect of Consumption of Kepok Banana (Musa Paradisiaca Formatipyca) on Reducing the Intensity of Nausea, Vomiting in 1st Trimester Gravida Women - Suci Anggraeni; Luvi Susiana; Reni Yuli Astutik; Nining Istighosah; Yenny Puspitasari (Universitas STRADA Indonesia, 2025)
Background: Nausea and vomiting in early pregnancy is something that is normal for all pregnant women to experience as long as the intensity is not excessive. This has an impact on pregnant women and also the fetus, causing fluid, nutrition and weight loss. Purpose: The aim of this study was to determine the effect of consuming Kepok bananas (Musa Paradisiaca Formatypica) on reducing the intensity of nausea and vomiting in women in first trimester gravida. Methods: This study used a pre-experiment design with one group pre-post test in which pregnant women were given boiled kepok bananas for 40 minutes 3 times a day for 7 days. The population in this study was pregnant women in the first trimester who experienced nausea and vomiting. The sample size was 36 respondents. . The sampling technique uses random sampling. The independent variable is consumption of kepok bananas while the dependent variable is intensity of nausea and vomiting. This research uses a questionnaire with Wilcoxon test data analysis Result: The results of the research showed that before being given Kepok bananas, the majority (75.0%) experienced moderate nausea and vomiting, as many as 27 respondents. After being given Banana Kepok, most of the 18 respondents (50.0%) did not experience nausea and vomiting. Based on the results of statistical tests, it is known that the p value is 0.000. Because the value of 0.000 is smaller than <0.05, it can be concluded that the